The political basis of economic development : an exploration in comparative political analysis - Holt, Robert T.; Turner, John Elliot; University of Minnesota (Princeton, N.J. : Van Nostrand, 1966)
This book is on economy development and the economic basis
"A study from the Center for Comparative Political Analysis, Department of Political Science, University of Minnesota."
Erratum leaf inserted.
includes index.
Includes bibliographical references
oo 30/08/2018
Loans
Keywords: Economic policy; State; Comparative government; Economic development